Expert Evidence in Criminal Proceedings: New Practice Within Old Normative Frameworks and Other Problems - Soković, Snežana (Zbornik Instituta za kriminološka i sociološka istraživanja, 2008)
Actual problems of expert evidence in criminal proceedings show that the contribution of this, almost regular part of criminal procedure, "a dominant evidence, an evidence that is always much expected of" to the effective and reliable results of criminal proceedings is greatly obstructed by a discordance of contemporary demands, new practice and old normative frameworks. A need for expert evidence in court proceedings arises when the court lacks the necessary expert knowledge needed for establishing all relevant facts and rendering a final decision; therefore, it summons a forensic expert to establish the needed facts by applying his/her expert knowledge. In such circumstances, a court with its formal procedural authority to bring the court’s decision, but without the necessary expert-specialised knowledge, and a forensic expert with the needed expert knowledge and the real possibility to determine a court decision essentially, but without formal competences to bring decisions in criminal matters, are brought face to face. Legal regulation of expert evidence should enable this evidence, most often "the evidence that makes a decision", to maximally contribute to an effective and reliable establishment of relevant facts. However, the practice shows that precisely that evidence very often slows down, complicates and dilutes the demonstrative process. It seems that legislative interventions aimed toward making a modern and effective criminal procedure, not so rare during the past decade, have evaded expert evidence issues. Taking the proofs into consideration by expert evidence within a criminal procedure still points out many controversial matters justly presumed to affect essentially the quality of setting the controversial legally relevant facts, as well as of unjustified delays in criminal proceedings. Some of these issues relate to irregularities in the operation of criminal procedure agencies, while others concern a need to reconsider present solutions in the primary and supplementary procedural legislation. For quite a long time, these issues have been observed as controversial but still stay unsolved and untouched by (long-term) criminal legislature reform, in spite of producing lengthy and low-quality expert evidence. Meanwhile, there is arising and consolidating a "new" practice of socalled private expert evidence in criminal proceedings although incompatible into present normative framework.